2020
DOI: 10.14349/rlp.2020.v52.17
|View full text |Cite
|
Sign up to set email alerts
|

Face-to-face Assessment of COGTEL in Adolescents: Test-Retest Reliability and Association with School Grades

Abstract: The Cognitive Telephone Screening Instrument (COGTEL) has shown to be a brief, reliable, and valid instrument to assess cognitive functioning in adults in face-to-face procedures as well as over the phone. So far, no psychometric evaluation exists on its use in adolescents. The present study set out to evaluate the psychometric properties of the face-to-face application of the COGTEL in adolescents in the school context and to analyse the association with school grades. We assessed cognitive performance using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…CP was assessed through structured interviews using the Cognitive Telephone Screening Instrument (COGTEL) [ 23 , 31 , 32 , 33 ], validated for adolescents [ 33 ]. THE COGTEL [ 23 , 31 , 32 , 33 ] includes the following cognitive tasks: (i) prospective memory, (ii) verbal short-term memory, (iii) verbal long-term memory, (iv) working memory, (v) verbal fluency, and (vi) inductive reasoning. The total score results from aggregating the six tasks ( Table 1 ).…”
Section: Methodsmentioning
confidence: 99%
“…CP was assessed through structured interviews using the Cognitive Telephone Screening Instrument (COGTEL) [ 23 , 31 , 32 , 33 ], validated for adolescents [ 33 ]. THE COGTEL [ 23 , 31 , 32 , 33 ] includes the following cognitive tasks: (i) prospective memory, (ii) verbal short-term memory, (iii) verbal long-term memory, (iv) working memory, (v) verbal fluency, and (vi) inductive reasoning. The total score results from aggregating the six tasks ( Table 1 ).…”
Section: Methodsmentioning
confidence: 99%
“…Cognitive function was assessed through an interview using the Cognitive Telephone Screening Instrument. The Cognitive Telephone Screening Instrument (COGTEL) [ 31 , 32 , 33 ] included six cognitive tasks: (1) Prospective memory—assessed using an event-based task (i.e., a task in which the execution of the intended action is triggered by the presentation of a specific external cue). The formation of the intention occurred at the beginning of the test interview (0 or 1 point).…”
Section: Methodsmentioning
confidence: 99%
“…Members of the field team administered the questionnaire during face-to-face interviews. A detailed description of the evaluation procedures, namely procedures and scoring, can be found in Ihle et al [ 31 ], Gouveia et al [ 32 ] and Kliegel et al [ 33 ]. Memory is used to describe the cognitive mechanism by which information is acquired, retained, and recalled.…”
Section: Methodsmentioning
confidence: 99%
“…Subsequent research has confirmed the COGTEL as a valid and reliable assessment of cognitive functioning, also in terms of allowing a more fine-grained differentiation within the range of healthy cognitive development (Ihle et al 2017 ). Moreover, several large-scale studies in epidemiological, aging, and pedagogical research have used the COGTEL so far (e.g., Breitling et al 2010 ; Gouveia et al 2020 ; Vallet et al 2020 ), which further underlines its great flexibility and simple integration into a variety of research contexts.…”
Section: Assessing Cognitive Functioning Outside Of the Laboratorymentioning
confidence: 99%